EMERGENCY STATES IN ARTERIAL HYPERTENSION - M. A. Gurevich; N. A. Kuz’menko (Alʹmanah Kliničeskoj Mediciny, 2016)
The article describes in detail potential emergency states in patients with different stages of arterial hypertension with special attention to diagnosis and rational management of hypertensive crisis. Differentiated approach to management of different forms of hypertensive crisis is specified.